Astrin: A Key Player in Mitosis and Cancer - Ying, Zhenguang; Yang, Jing; Li, Wei; Wang, Xia; Zhu, Zeyao; Jiang, Weipeng; Li, Chunman; Sha, Ou (Frontiers in Cell and Developmental Biology, 2020)
Astrin, which is a spindle-associated protein, was found to be closely related to mitotic spindle formation and maintenance. It interacts with other spindle-related proteins to play a key role in maintaining the attachment of the kinetochore-microtubule, and ensuring accurate segregation of the chromosomes, and the timely onset of anaphase. In addition, Astrin was quite recently found to be abnormally expressed in a variety of cancers. Astrin promotes the occurrence and metastasis of cancer by participating in various molecular pathways, and is considered an important prognostic and survival predictor.